Involvement of the Nrf2 Pathway in the Regulation of Pterostilbene-Induced Apoptosis in HeLa Cells via ER Stress - Bo Zhang; Xiao-Qin Wang; Han-Yin Chen; Bin-Hua Liu (Elsevier, 2014)
Abstract.: Among the various cancer cell lines, HeLa cells were found to be sensitive to pterostilbene (Pte), a compound that is enriched in small fruits such as grapes and berries. However, the mechanism involved in the cytotoxicity of Pte has not been fully characterized. Using biochemical and free radical biological experiments in vitro, we identified the pro-apoptotic profiles of Pte and evaluated the level of redox stress-triggered ER stress during HeLa cell apoptosis. The data showed a strong dose-response relationship between Pte exposure and the characteristics of HeLa apoptosis in terms of changes in apoptotic morphology, DNA fragmentation, and activated caspases in the intrinsic apoptotic pathway. During drug exposure, alterations in the intracellular redox homeostasis that favor oxidation were necessary to cause ER stress- related apoptosis, as demonstrated by enzymatic and non-enzymatic redox modulators. A statistically significant and dose-dependent increase (P < 0.05) was found with regard to the unique expression levels of Nrf2/ARE downstream target genes in HeLa cells undergoing late apoptosis, levels that were restored with anti-oxidant application with the Pte treatment. Our research demonstrated that Pte trigged ER stress by redox homeostasis imbalance, which was negatively regulated by a following activation of Nrf2.[Supplementary Figure and Table: available only at http://dx.doi.org/10.1254/jphs.14028FP] Keywords:: apoptosis, ER-stress, HeLa cell, pterostilbene, redox homeostasis